2021
DOI: 10.2147/ijgm.s331387
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Primary Sleep Disorders and Temporomandibular Disorders: An 8-Year Nationwide Cohort Study in South Korea

Abstract: Background While evidence is accumulating to propose a specific contribution of sleep disorders and low quality sleep in the pathogenesis of temporomandibular disorders (TMD), management of primary sleep disorders in the process of preventing and treating TMD still remains scientifically unsupported. Objective To investigate the association of primary sleep disorders with TMD risk in South Korea. Patients and Methods This study was based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…The accumulating evidence supports the intimate relationship between physical activity, sleep quality, and systemic inflammation which are all factors known to influence TMD symptoms in previous literature [71][72][73][74]. Through this prospective study based on objective physical activity measurements in a well-defined patient group of TMD, the resulting data will be able to support the establishment of a clinical guideline related to physical activity recommendations and the diagnostic value of such measurements in TMD prognosis.…”
Section: Discussionsupporting
confidence: 71%
“…The accumulating evidence supports the intimate relationship between physical activity, sleep quality, and systemic inflammation which are all factors known to influence TMD symptoms in previous literature [71][72][73][74]. Through this prospective study based on objective physical activity measurements in a well-defined patient group of TMD, the resulting data will be able to support the establishment of a clinical guideline related to physical activity recommendations and the diagnostic value of such measurements in TMD prognosis.…”
Section: Discussionsupporting
confidence: 71%
“…Because, sleep during weekdays could be influenced by diverse factors, including work, school and so on, sleep duration during weekends would be more valid factors to determine quality of the sleep. The association between insomnia and facial pain has been demonstrated, previously 15 - 19 . Patients with both TMD and insomnia with objective short sleep duration endorsed higher self-reported pain severity and functional limitation of the jaw 17 and the prevalence of primary insomnia was higher in patients with myofascial TMD compared to that in controls 15 .…”
Section: Discussionmentioning
confidence: 98%
“…Reducing total sleep time could affect pain severity and morning pain expectancy 18 . Moreover, an eight-year cohort study suggested that primary sleep disorder could be an important independent risk factor for the initiation and maintenance of TMD 19 , and treatment of underlying insomnia could result in improved chronic orofacial pain 20 . Hence, sleep deprivation may interact with the perception of chronic facial pain; however, the role of OSA in the development of chronic facial pain could not be assumed from this study.…”
Section: Discussionmentioning
confidence: 99%
“…Group classification was based on presence or absence of 3 categories of systemic issues: pain-related issues, psychological issues, and sleep-related issues. The 3-category construct was created based on previously identified major risk domains for TMDs 30,41,43,80,83,97,121 and for ease of conceptualization and application in clinical practice. The items were selected from the health history report because they do not depend on clinical training or clinician judgement and therefore are easily generalizable to general dentistry or primary care settings.…”
Section: Group Classificationmentioning
confidence: 99%